Remaking the real economy : escaping destruction by organised money - Pearson, Gordon (Bristol : Policy Press, 2020)
Debunking the myths around the current economic belief systems, this book reveals how mainstream perspectives work for the benefit of the organised money establishment, while causing all manner of destructions, inequalities and frauds, all conspiring against the common good. Focused on the realities of organisational systems, Pearson offers a practical alternative to economic dogma. Written from a distinctive perspective that combines practitioner and academic expertise, this book is structured as a simple model of business strategy and identifies necessary systems change in order to achieve a truly sustainable future.
Title from publisher's bibliographic system (viewed on 23 Jun 2021).
Keywords: Economics